UJI BEBERAPA KONSENTRASI EKSTRAK DAUN MIMBA (Azadirachta indica A. Juss) UNTUK MENGENDALIKAN HAMA ULAT PENGGULUNG DAUN (Strepsicrates sp.) PADA TANAMAN EUKALIPTUS (Eucalyptus sp.) DI PEMBIBITAN - Saputri, Marisha; Rustam, Rusli; Salbiah, Desita (Jurnal Agroekoteknologi, 2020)
Leaf-rolling caterpillars (Strepsicrates sp.) are the main pests that attack eucalyptus plants during breeding. Pest Control Strepsicrates sp. still using synthetic chemical pesticides. The impact of the use of synthetic chemical pesticides is harmful to the environment, so the use of vegetable pesticides from neem leaf extracts is an alternative in pest control Strepsicrates sp. This study aimed to obtain an extract of neem leaves which is effective in controlling the pest Strepsicrates sp. in eucalyptus plants. This research was conducted in the experimental garden and pest laboratory of the Faculty of Agriculture, Riau University. The study used a completely randomized design (CRD) with 6 treatments and 4 replications, to obtain 24 units of the experiment. Each unit ofexperiment was infested with 10 larvae of Strepsicrates sp. instar 3. The treatments given are some concentrations of neem leaf extracts namely M0: 0 gl-1 water, M1: 20 gl-1 water, M2: 40 gl-1 water, M3: 60 gl-1 water, M4: 80 gl- 1 water, M5: 100 gl-1 water. The parameters observed were initial time of death, daily mortality, total mortality, attack intensity, and daily air temperature and humidity at the study site. Data were analyzed statistically using analysis of variance and further tests with Honestly Significant Difference (BNJ). The results showed that neem leaf extract with a concentration of 40 g.l-1 water was effective in killing Strepsicrates sp. with a percentage of total mortality of 91.67%.Â Keyword: Strepsicrates sp., Eucalyptus, Neem leaf extract